Bilateral comparison of liquid paraffin and cream base on transepidermal water loss among psoriasis patients: A randomized trial - Chutima Churee (2019)
© 2018, Medical Association of Thailand. All rights reserved. Background: Psoriasis is a common chronic inflammatory disease. Psoriasis lesions have water-holding and show increased transepidermal water loss (TEWL). Patients experience pain, discomfort, and skin dryness or dehydration. Skin moisturizing is a major component of treatment for these patients to maintain the smoothness of the skin and to break the dry-skin cycle. Objective: To compare the skin moisturizing efficacy of liquid paraffin (LP) with cream base (CB) on TEWL and skin hydration on normal and psoriasis lesions of psoriasis patients. Materials and Methods: The present study was conducted among 100 participants with Psoriasis Area and Severity Index (PASI) score less than 10. Participants aged 18 years or older who visited the Outpatient Department of Institute of Dermatology were randomly selected to have the substances applied on normal skin and psoriasis lesions twice daily with LP on one side and CB on the other side. TEWL and skin hydration were measured at baseline and after application at the end of the fourth week. Results: There were 48 females and 52 males, with the mean (SD) age of 45 (13) years and average duration of psoriasis of 12 years. For normal skin, TEWL at the end of 4-week treatment period significantly decreased in areas applied with LP compared to CB (median change from baseline-0.30 g/m²/hour versus 0.30 g/m²/hour, respectively, p=0.01). For psoriasis lesions, change of TEWL was not different between the two agents (p=0.22). Regarding skin hydration after four weeks of treatment, there was no statistically significant difference between LP and CB in normal skin (change from baseline of 5.04 AU for LP and 4.20 AU for CB). For psoriasis lesions, skin hydration increased more significant with CB than with LP (change from baseline 4.00 AU for CB versus 2.65 AU for LP, p<0.01). Conclusion: For the patients with plaque type psoriasis, LP reduced TEWL more than CB in normal skin, but CB increased skin hydration more than LP in psoriasis lesions.